The Relationship Between Some Complete Blood Count Parameters and Myocardial Perfusion: A Scintigraphic Approach - Semra Ozdemir; Ahmet Barutcu; Emine Gazi; Yusuf Tan; Hakan Turkon (World Journal of Nuclear Medicine)
Recent studies have shown that there is a relationship between some inflammatory and biochemical markers derived from complete blood count (CBC) such as neutrophil/lymphocyte (N/L) ratio, platelet/lymphocyte (P/L) ratio, platelet distribution width (PDW), red blood cell distribution width (RDW), and coronary artery disease (CAD). The aim of this study was to determine N/L ratio, P/L ratio, PDW values, and RDW values, which are associated with myocardial perfusion in patients diagnosed with CAD. This study included 262 patients (149 with myocardial ischemia/infarction and 113 with normal myocardial perfusion) undergoing myocardial perfusion scintigraphy (MPS) with CBC within 90 days of MPS. Myocardial perfusion parameters such as summed stress score and summed difference score (SDS) were compared with N/L ratio, P/L ratio, PDW values, and RDW values. Neutrophil counts and N/L ratios were significantly higher in patients diagnosed with myocardial ischemia and/or infarct. However, there was no statistically significant relationship between myocardial perfusion abnormalities and P/L ratio, PDW values, and RDW values. This study showed that N/L ratio is related to myocardial ischemia/infarction and correlated to left ventricular ejection fraction (LVEF).